Penguatan Moderasi Beragama melalui Pembinaan Kesadaran Beragama di MA Integratif NU Al-Hikmah Jeru Tumpang - Ida Rofi’Unnur Rodiah; Anas Tania Januari (Journal Islamic Studies, 2025)
Islam is Rahmatan lil 'alamin, which means Islam brings peace and compassion to all of humanity and the universe. By understanding this concept, one can easily maintain peace in the midst of diversity in society. Through Islamic education, Rahmatan lil'alamin can shape noble character, practice Islamic teachings in moderation and instill the values of civility, tolerance, togetherness, and compassion in the midst of existing diversity. MA Integrative NU Al-Hikmah Jeru Tumpang, Malang Regency, in shaping the character of rahmatan lil'alamin students by building religious awareness which then becomes a provision in implementing a moderate religious attitude. Religious awareness becomes a guide in individual and social life, to create a life that is hablumminallah and hablumminannas in accordance with the command of Allah SWT. This research was conducted through observation, interviews, and documentation. The results showed that the cultivation of religious awareness at the NU Al-Hikmah Jeru Integrative High School used the methods of lectures, learning the Koran, and reciting dhikr, containing the principles of religious moderation, namely Tawasuth, Tawazun, I'tidal, Tasamuh, Musawah, and Shura. The results of fostering religious awareness can be seen from several activities that have been carried out, which include the fulfillment of religious moderation indicators, namely indicators of national commitment, tolerance, anti-radicalism, and accommodating local culture.